The Legal Consequence Of The Judge Decision In The Case Of Children Criminal Justice Which Do Not Based On Society Research From Society Supervisor (Studies on Settlement Case of Children Crime In State Court of Cirebon) - Tasmo Tasmo; Rakhmat Bowo Suharto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
This study to answer the question: 1) The legal consequences of the Juvenile Judge decision who do not based the Society Research (Litmas) of Society Supervisor (PK) in the State Court of Cirebon, 2) The value of justice verdict child in considering Society Research (Litmas) of Society Supervisor (PK) in the State Court of Cirebon.The approach used in this study is a sociological juridical approach. The kind of this research is descriptive analysis. Data were collected by interview and literature method. The method used by researchers is sociological approach juridical law and specification in this study were included descriptive analysis. As for sources and types of data in this study are primary data obtained from interviews with field studies State Court of Cirebon, and secondary data obtained from the study of literature.The final conclusion is: 1) The legal consequences of the judge's decision not to consider children who Litmas Results PK Bapas under Article 60 of Child Law Criminal Justice System, child verdict is declared null and void, and the cancellation do not require cancellation; 2) Society Research (Litmas) Society Supervisors (PK) Correctional Center did not bring a positive impact to deliver a fair verdict and best for the child, when the judge makes it just as a mere formality and not as consideration verdict. Put forward suggestions: 1) It should be implemented in law changes SPPA clearly so Litmas PK Bapas not only as a formal requirement child judges in decisions; 2)Institutions should set up an oversight judge to judge that the judge's ruling the child can be declared as null and void the decision, and the judge supervision should stipulate that convicted child can not be executed by the Public Prosecutor.Keywords: Law Effects; Judge Decision; Child Crime; Society Research; Society Supervisor.